Design and Development of an Automated Guided Vehicle (AGV) for Store and Warehouse Automation (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract—The development of Automated Guided Vehicles (AGVs) has revolutionized material handling in industrial and commercial settings. This project focuses on designing, devel-oping, and testing a prototype AGV for store and warehouse automation. The AGV utilizes an ESP32 microcontroller, infrared (IR) sensors for line-following, and an ultrasonic sensor for obstacle detection. The vehicle is designed to follow a fixed path marked by a black line on the floor while avoiding obstacles in real-time. Built using cost-effective components, this prototype serves as a scalable and adaptable solution for educational and industrial applications. The system’s performance was validated through a series of controlled tests, demonstrating successful navigation, obstacle avoidance, and payload transport capabil-ities. The project aims to address the limitations of manual material handling, such as inefficiency, safety risks, and high labor costs, offering a reliable and cost-effective alternative for indoor logistics. Future enhancements could include dynamic navigation, wireless communication, and advanced control al-gorithms to further optimize the AGV’s performance in more complex environments.